Design Culture in Liverpool 1888-1914 : the Origins of the Liverpool School of Architecture. - Crouch, Christopher (Liverpool University Press, 2002)
By the 1930s the Liverpool School of Architecture was the most famous British school of architecture in the world, promoting modern architecture and city planning internationally. This book looks at the cultural environment in Liverpool at the turn of the twentieth century which enabled such an important institution to come to fruition. It examines attitudes towards design practice through the work of patrons, practitioners, institutions and theorists in the city, and considers the way their ideas were formed by national and international trends. From a city microcosm of contesting design aest.